2005
DOI: 10.4103/0970-4388.16444
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Chandigarh sports coaches regarding oro-facial injuries and their prevention

Abstract: Enthusiastic participation by the younger generation in sports exposes them to a high risk of injuries. In the present study, the perceptions of sports coaches regarding their knowledge and experience of such injuries is evaluated. The coaches considered helmet as the most common protective device followed by mouth guard and facemask. About 58% observed that boxing was associated with oro-facial injuries and protective devices were deemed mandatory by 68% in this event. About 45% saw over five injuries in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Sports teachers have not only the responsibility of educating the sports persons about protective devises but also help them in motivating for its regular use. Studies have shown that although the sports teachers have adequate knowledge of protective devices, few imply it in their regular practice [17,18]. Similar results have been observed by the present study, wherein only 3% of the sports teachers recommended the use of mouth guards.…”
Section: Discussionsupporting
confidence: 88%
“…Sports teachers have not only the responsibility of educating the sports persons about protective devises but also help them in motivating for its regular use. Studies have shown that although the sports teachers have adequate knowledge of protective devices, few imply it in their regular practice [17,18]. Similar results have been observed by the present study, wherein only 3% of the sports teachers recommended the use of mouth guards.…”
Section: Discussionsupporting
confidence: 88%
“…Adolescents and children, in particular, are made aware of this issue earlier than used to happen in the past. An Irish and an Italian study investigated mouthguard wearing to prevent sports‐related dental injuries in children and youngsters . These studies confirm the early wearing of mouthguards by children and youngsters during school sports or at sports clubs.…”
Section: Discussionmentioning
confidence: 73%
“…These studies confirm the early wearing of mouthguards by children and youngsters during school sports or at sports clubs. They also emphasize the need for greater prevention in this area .…”
Section: Discussionmentioning
confidence: 99%
“…70% of the coaches in the present study found the frequency of oro-facial injuries between 1-5 and 70% of these injuries were mostly due to non-use of protective devices. In a similar study by Lehl G, 40% of the coaches found the frequency of injury between1-5 [32]. Authors who found the frequency of injury due to non-use of protective devices were 82% by Lehl [32,33,34,35].…”
Section: Discussionmentioning
confidence: 78%